Průkaz energetické náročnosti budovy - Lněnička, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Bakalářská práce je zaměřena na hodnocení energetické náročnosti Hotelu Mars ve Špindlerově Mlýně. Teoretická část pojednává o přeměně slunečního záření na elektrickou energii využitím fotovoltaiky. Výpočtová část analyzuje energetické potřeby a toky hodnocené budovy. Výsledkem je průkaz energetické náročnosti budovy, umístěném do části C.

This bachelor thesis deals with the evaluation of the energy performance of the Mars hotel in Špindlerův Mlýn. The theoretical part of this thesis is focused on the conversion of sunlight into electric power using solar-powered photovoltaics. The practical part is focused on the analysis of energy consumption and energy flux of the inspected building. The final part C concerns about the result of this thesis – the energy performance certificate of the analyzed building.
Energy Performance Certificate of the Building
Keywords: Energetická náročnost budovy; PENB (Průkaz energetické náročnosti budovy); hotel; fotovoltaika.; Energy performance of building; building energy performance certificate; hotel; photovoltaics